SAMANNTHA WHITE’S STRUGGLE IN JUSTIN SIMIEN’S DEAR WHITE PEOPLE (2014) FILM - Nasrullah, Nasrullah; Dyrata, Halwin Esa Ikrar (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni dan Budaya, 2020)
ABSTRACTRacism is still common in human life today. Racism usually occurs when blacks are bullied or otherwise mistreated by whites. This can make blacks strong enough and claim equal rights in public. As a reflection of real life, one of the films that fight for equal rights (anti-racism) is the Dear White People film. This research aims to analyze the struggles of the characters in the Dear White People film, where blacks demand that there is no mixing of whites and blacks because the environment on the Wenchester campus is mostly black. In this research, researcher used qualitative methods. In this research, researcher took data through conversations carried out by characters in the Dear White People film. The results of the research were the data collected by the researcher only obtained three of the five analyzes.Keywords: racism, struggle, film